Microvascular Free Flaps for Reconstruction of Postmucormycosis Head-and-Neck Defects: Experience in a Tertiary Care Institute - Ashikesh Kundal; Amit Sharma (Journal of Head & Neck Physicians and Surgeons, 2024)
Mucormycosis or black fungus raised to infamy during the COVID-19 epidemic all over the world with disastrous consequences including death. Those who survived were left with complex deformities mostly involving the head-and-neck region. We through this article would like to present our experience of management of head-and-neck defects in patients of mucormycosis both in acute and delayed presentations using microvascular free flap reconstruction.